Analisis Kawin Paksa Dalam Perspektif Hukum Islam - Ahmad Muhammad Mustain Nasoha; Nadia Khoirotun Nihayah; Alfina Arga Winati (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
Marriage is not only based on a birth bond between a man and a woman, because marriage is not just a matter of worshiping Allah SWT but also to obtain happiness, peace of mind, and to continue the lineage. This research discusses aims to explore more broadly the causes, impacts and analysis of forced marriages caused by arranged which are viewed from an Islamic legal perspective. The method used in this research is a qualitative method as to obtain information through interviews with various elements of society and through field observations. The result of this research show that the factors that cause forced marriage to occur in society are parental, economic, educational, and customary factors. The practice of forced marriage has negative impacts such as divorce, family conflict, and can lead to infidelity. So it can be emphasized that forced marriage is prohibited in Islamic law.